Desenvolvimento de arranjo de antenas reconfigur?veis - Costa, Igor Feliciano da (2013)
This work reports the development of reconfigurable antenna arrays, for wireless networks applications on 5,8GHz and 2,4 for tracking and real time data transmission with Unmanned Aerial Vehicles (UAV). We used two techniques for reconfiguration, using photoconductive switches and delayed imput power signals. Six antennas have been developed, the first antenna is a E-shaped slot antenna with optically controlled resonance frequency bands, between 2,4GHz and 5,8GHz ISM and maximum gain 5dBi. From this antenna arrays, we developed over three antennas, using two or three ground planes reflectors. The use of ground planes, increased the gain by 10, 12,5 and 16dBi respectively. The second array has been developed for use in UAV 's, for establishing real time datalinks to the ground control base. The antenna was developed through a waveguide with an slots array, which are controlled by optical switches, allowing the radiation pattern reconfiguration for a transmission in any radial. The ability to radiate for different directions, optimize the efficiency of datalink, in order to transmit only for the desired location to maximize its gain and increasing the distance of the link. The final antenna has a maximum gain of 7.8 dBi for 5,8GHz with a bandwidth of 8.33%. The last antenna was been developed for traking UAV?s by adapting the positioning and polarity of its radiation pattern, collecting data such as speed and altitude, may also increase the main lobe gain enabling real-time data link to the aircraft. Through an innovative pyramidal horn antennas array and a custom monopulse feeder, three different radiation patterns can be obtained. The feeder is responsible for implementing the delay to the feed signal. A paraboloid was used to increase the gain, thereby constituting a parabolic antenna monopulse that possesses 28dBi minimum gain and 31dBi maximum at 5,8GHz.